Cultivating Identities: The Catholic School as Diverse Ecclesial Space - McDonough, Graham P. (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2016)
I argue that the crisis of identity Catholic schools are experiencing in the 21st century also presents an opportunity for a rediscovery and expanded conversation, both within and beyond the confines of the institutional Church, of what it means to exist separately from the mainstream without restricting internal diversity.  I begin by presenting salient historical, theological, and sociological features Catholicism and Catholic Education during and since the Second Vatican Council (1962-5) to establish the context and substance of its modern identity crisis.  I then provide a review of current controversies within Catholic schools to demonstrate how they are symptomatic of this crisis, but also potential catalysts for exploring new options. The next section argues both for the merits of recognizing multiple Catholic identities, and imagining the Catholic school as an institution that assembles and coordinates them.  I propose that the fact of multiple Catholic identities should be interpreted as differences in kind, rather than by their degree of difference from a narrowly constructed idea of Catholicism.  I also propose that the intersection of these identities at school should be encouraged as a way of nurturing both students’ own identities and their ability to encounter religious difference within their own tradition and community.  The conclusion demonstrates how in practice this model presents a promising means of possibly deepening individual and institutional religious identit(y/ies) in today’s world, and for responding to controversial issues that arise within Catholic schools.